2003
DOI: 10.1002/ejic.200200652
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic, 57Fe Mössbauer, and IR Monitoring of the Thermal Spin Transition in a New Family of Iron(II) Spin‐Transition Complexes

Abstract: A new family of iron(II) tetrafluoroborate and perchlorate spin-crossover compounds has been synthesised and is discussed. The iron(II) ion is surrounded by six 1-ethyltetrazole ligands, which are halogen-substituted on the C2 atom of the ethyl group. The spin-crossover temperatures T 1/2 are high compared to the unsubstituted (1-alkyltetrazole)iron(II) complexes. The shape of the spin-transition curve (i.e. γ HS vs. T) varies largely over the different complexes and appears to be influenced neither by the cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…This choice was justified by the observation that the spin transition is present in iron(II) complexes of 1-substituted tetrazoles with perchlorate or tetrafluoroborate as counteranions. [25,35,36] Spin crossover is exhibited by monomeric complexes based on alkyl, [35,37] cycloalkyl [38] and fluorinated alkyl tetrazoles [36,39] as well as polymeric systems containing bis- [22][23][24] and tris-tetrazoles [26] as bridging ligands. In the present study, the magnetic behaviour of 1·BF 4 differs completely from that observed for the perchlorate analogue.…”
Section: Introductionmentioning
confidence: 99%
“…This choice was justified by the observation that the spin transition is present in iron(II) complexes of 1-substituted tetrazoles with perchlorate or tetrafluoroborate as counteranions. [25,35,36] Spin crossover is exhibited by monomeric complexes based on alkyl, [35,37] cycloalkyl [38] and fluorinated alkyl tetrazoles [36,39] as well as polymeric systems containing bis- [22][23][24] and tris-tetrazoles [26] as bridging ligands. In the present study, the magnetic behaviour of 1·BF 4 differs completely from that observed for the perchlorate analogue.…”
Section: Introductionmentioning
confidence: 99%
“…[11,16] The series member [Fe(chloroethyltetrazole) 6 ](BF 4 ) 2 (1) shows a two-step spin transition between 300 and 90 K and it was hypothesized that two high-spin (HS) fractions of Fe II may exist with different crystallographic positioning and behavior during the spin transition. [11] A crystal structure determination of the HS structure from powder diffraction data revealed Fe II to be in a special position, but no evidence was found for different HS Fe II fractions.…”
Section: Introductionmentioning
confidence: 99%
“…[11,16] The series member [Fe(chloroethyltetrazole) 6 ](BF 4 ) 2 (1) shows a two-step spin transition between 300 and 90 K and it was hypothesized that two high-spin (HS) fractions of Fe II may exist with different crystallographic positioning and behavior during the spin transition. [11] A crystal structure determination of the HS structure from powder diffraction data revealed Fe II to be in a special position, but no evidence was found for different HS Fe II fractions. [17] The plateau in the transition curve has also been explained by the assumption that extra thermodynamic stabilization takes place when 50 % of the Fe II ions are in the HS state and 50 % in the low-spin (LS) state, [18] and in two recent articles this stabilization was attributed to the existence of regular structures of alternating HS and LS molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,[4][5][6][7][8][9] A wide range of spin crossover has been observed experimentally, for example, gradual complete, two-step transitions, incomplete transitions with a residual high-spin (HS) species at low temperature, and hysteresis loops. [10][11][12][13] Most of the studies of spin crossover have concentrated on iron(ii) compounds. [14,15] Thermal spin crossover in coordination compounds of the form [Fe(alkyltetrazole) 6 ](X) 2 (with X = BF 4 À , ClO 4 À ) were first described by Franke.…”
Section: Introductionmentioning
confidence: 99%